2018
DOI: 10.1016/j.jid.2017.07.839
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Mediates Nilotinib Response in KIT-Altered Melanoma: A Phase II Multicenter Trial of the French Skin Cancer Network

Abstract: Mutated oncogenic KIT is a therapeutic target in melanoma. We conducted a multicenter phase II trial on the KIT inhibitor nilotinib in patients with unresectable melanoma harboring KIT alteration. The primary endpoint was the response rate (complete response or partial response following Response Evaluation Criteria in Solid Tumors criteria) at 6 months. Pharmacodynamic studies using KIT sequencing, qPCR array, and immunostaining of downstream KIT effectors were performed during treatment. Twenty-five patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 46 publications
4
38
0
Order By: Relevance
“…63 Five studies were conducted using this drug, in which all patients received orally nilotinib 400 mg twice a day. 56,[64][65][66][67] The most recent study was a phase II clinical trial conducted by the French Skin Cancer Network on 25 patients. 65 At 6 months after nilotinib initiation, only four patients were responsive to nilotinib (ORR: 16%, 90% CI: 5.6-33.0%), including one CR patient and three PR patients.…”
Section: Nilotinibmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Five studies were conducted using this drug, in which all patients received orally nilotinib 400 mg twice a day. 56,[64][65][66][67] The most recent study was a phase II clinical trial conducted by the French Skin Cancer Network on 25 patients. 65 At 6 months after nilotinib initiation, only four patients were responsive to nilotinib (ORR: 16%, 90% CI: 5.6-33.0%), including one CR patient and three PR patients.…”
Section: Nilotinibmentioning
confidence: 99%
“…56,[64][65][66][67] The most recent study was a phase II clinical trial conducted by the French Skin Cancer Network on 25 patients. 65 At 6 months after nilotinib initiation, only four patients were responsive to nilotinib (ORR: 16%, 90% CI: 5.6-33.0%), including one CR patient and three PR patients. Out of the other 21 patients, six experienced progression and 15 died with an estimated PFS of 6.0 months and a median OS of 13.2 months (95% CI: 5.6-19.9 months).…”
Section: Nilotinibmentioning
confidence: 99%
“…Treatment with KIT inhibitors resulted in a trend toward improved response in melanoma patients, with response rates of approximately 20%. Despite the clinical benefit achieved with KIT inhibition in select patients with melanoma harboring KIT mutations, most patients ultimately experience disease progression [9,10,11,12,13,14]. Immunotherapy has recently emerged as a promising treatment modality for cutaneous melanomas.…”
Section: Introductionmentioning
confidence: 99%
“…Several trials based on targeting with kinase inhibitors c-KIT showed consistent results, obtaining an ORR of 16-29% and a median OS of 12-13 months [7][8][9][10]. Other studies investigating nilotinib, a small molecule more potent than imatinib in inhibiting KIT, showed promising clinical activity [11,37,38]. The global, single-arm, phase II TEAM trial showed 26.2% ORR (all partial responses) and OS of 18 months [11].…”
Section: Kitmentioning
confidence: 80%